2008
DOI: 10.1162/pres.17.6.527
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Audio Systems

Abstract: To be immersed in a virtual environment, the user must be presented with plausible sensory input including auditory cues. A virtual (three-dimensional) audio display aims to allow the user to perceive the position of a sound source at an arbitrary position in three-dimensional space despite the fact that the generated sound may be emanating from a fixed number of loudspeakers at fixed positions in space or a pair of headphones. The foundation of virtual audio rests on the development of technology to present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Articles presenting mathematical models or correction algorithms are not considered in this review, as it is focused on empirical user studies. Further, only research on visual virtual environments is discussed here; for distance perception in auditory virtual environments, see, for example, Kapralos et al [2008], Loomis et al [1999], or Zahorik et al [2005; for distance perception in visual augmented reality, see, for example, Kruijff et al [2010] or Swan II et al [2007].…”
Section: Getting Virtual: a First Overviewmentioning
confidence: 99%
“…Articles presenting mathematical models or correction algorithms are not considered in this review, as it is focused on empirical user studies. Further, only research on visual virtual environments is discussed here; for distance perception in auditory virtual environments, see, for example, Kapralos et al [2008], Loomis et al [1999], or Zahorik et al [2005; for distance perception in visual augmented reality, see, for example, Kruijff et al [2010] or Swan II et al [2007].…”
Section: Getting Virtual: a First Overviewmentioning
confidence: 99%
“…To include both auditory and visual cues in our environment, we added a three-dimensional (3D) acoustic subsystem capable of synthesizing the spatialized sound associated with moving vehicles in real-time. Our spatialized audio rendering uses a nonindividual head-related transfer function (HRTF) (Begault, 1994;Kapralos et al, 2008), derived from the anthropomorphic audio logical research mannequin KEMAR (Knowles Electronics) (Gardner and Martin, 1995).…”
Section: The Roundabout Virtual Environmentmentioning
confidence: 99%
“…It has been shown that the spatial separation of simultaneously talking speakers improves their intelligibility, a phenomenon known as the "cocktail party effect" [18]. In addition to the implications on speech intelligibility, the externalisation is also considered to "add a pleasing quality" to virtual sounds [19]. In the present work the spatialisation is performed by applying a separate BRIR to each signal.…”
Section: Real-time Implementationmentioning
confidence: 99%